A Systematic Review of Challenges in Teaching and Learning Computer Programming Modules - Elegbeleye, Femi; Isong, Bassey (AI Society & STMIK Indonesia, 2025)
Computer programming has become an essential skill that is needed across many disciplines as it helps foster innovations like machine learning and artificial intelligence. Regardless of its significance, many students studying computer science and other disciplines often grapple with grasping basic programming language concepts, such as understanding logic, syntax, data structure, and data types. These challenges usually lead to very high rates of failure and loss of motivation among the students, therefore producing poor academic outcomes. This study investigates the unique programming challenges the students face, identifying some contributing factors and examining which challenges have more impact on the student. Moreover, it explores whether computing or non-computing students are more affected by these obstacles and reviews interventions to improve learning outcomes. The findings suggest best practices to enhance motivation and engagement in programming education, including introducing adaptive learning tools into the learning management systems, game-based applications, and AI-driven support systems personalized to meet each student's needs.